Clinico-epidemiological Profile of Colorectal Cancer in Oncology Department of Tertiary Centre Hospital in Nepal: An Observational Study - Rita Kumari Mahaseth; Rashika Upadhyaya; Prakash Chandra Panjiyar; Neha Jha; Ujjwal Kumar Jha (Journal of Nepal Medical Association, 2025)
Introduction: Colorectal cancer is a major global health concern with variable incidence and presentation across regions. The study was aimed to describe the clinic-epidemiological profile of colorectal cancer in a tertiary care hospital in Nepal. Methods: This observational cross-section study was conducted at a tertiary care hospital in Nepal from April 2021 to March 2024. Ethical clearance was obtained (Reference number: IRC/NMCTH/024/21). A total sampling method was used to include 69 patients with histologically confirmed colorectal cancer. Data were collected from patient records and analyzed using Statistical Package for the Social Sciences version 16.0. Point estimate at 95%Confidence Interval was calculated along with frequency and percentages for binary data, and mean and standard deviation for continuous data. Results: Out of 69 patients, 39 (56.52%) were male and 30 (43.48%) female. The most affected age group was 35–50 years, accounting for 26 (37.68%) patients. Rectum including recto-sigmoid colon was the most common tumor location in 38 (55.07%) cases. The most common presenting symptom was bowel habit change, seen in 46 (66.67%) patients. Lower anterior resection was performed in 26 (37.68%) cases. Histologically, moderately differentiated adenocarcinoma was the predominant type, found in 53 (76.81%) patients.